2022
DOI: 10.24815/jdab.v9i1.23618
|View full text |Cite
|
Sign up to set email alerts
|

Audit Tenure, Audit Independence, Audit Committee Independence, Board Independence, and Audit Quality in the Listed Deposit Money Banks in Nigeria: The Moderating Effect of Institutional Ownership

Abstract: The study examined the moderating effect of institutional ownership on relationship between audit tenure, audit independence, board independence and audit quality of listed deposit money banks (LDMBs) in Nigeria. The study population comprises 14 LDMBs on the Nigerian Stock Exchange as at 31st December, 2020. 13 LDMBs were used as sample of the study. Logit regression technique was used as a tool of data analysis. Findings of the study revealed that, in the direct relationship, audit independence, board indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
1
1
Order By: Relevance
“…This view is reasonable because longer tenure allows auditors to better understand the client's business and processes, which can improve the quality of their audits. This result also contradicts the findings of Bala (2022), who found that audit tenure significantly negatively impacts audit quality in Nigeria.…”
Section: Regression Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…This view is reasonable because longer tenure allows auditors to better understand the client's business and processes, which can improve the quality of their audits. This result also contradicts the findings of Bala (2022), who found that audit tenure significantly negatively impacts audit quality in Nigeria.…”
Section: Regression Resultscontrasting
confidence: 97%
“…They argue that other factors may be at play that impacts audit quality in SSA beyond just auditor tenure. Bala (2022) found that audit tenure has significant negative impact on audit quality in Nigeria. However, one potential gap in this study is that it only examines one country in Sub-Sahara Africa, and it is unclear whether these findings would hold true in other countries in the region.…”
Section: Audit Tenure and Audit Qualitymentioning
confidence: 98%
“…Penelitian (Kartika et al, 2019), bahwa auditor dengan sikap independensi yang tinggi akan menghasilkan audit yang bermutu, sebab mereka yang selalu mempertimbangkan fakta serta terdapatnya pertimbangan obyektif, dengan tidak memihak auditor dalam merumuskan serta memaparkan pendapatnya. Senada dengan penelitian (Haruna et al 2022) yang mengungkapkan bahwa, independensi pada auditor dengan sikap pengendalian serta pemantauan yang baik, berkontribusi pada kualitas audit yang baik. Karena itu berarti auditor benar-benar menetapkan sikap independensi dalam dirinya dalam menindaklanjuti tanggung jawabnya mengaudit.…”
Section: Pengaruh Independensi Auditor Terhadap Kualitas Auditunclassified
“…Moreover, in terms of competency, AC members with greater experience and industry expertise can easily discover any improper practices than members with less experience (Tanyi & Smith, 2015) and enable them to better understand the company's operation and financial circumstances, and subsequently be able to provide a better monitoring role (Alhababsah & Yekini, 2021). The agency theory proposes that AC independence mitigates agency costs (Haruna et al, 2022) as AC independence and monitoring roles improves effective supervision of management activities towards financial reporting (Adhikary & Mitra, 2016;Alkebsee et al, 2022). High AQ is linked to routine meetings of the AC (Khudhair et al, 2019;Gresia & Itan, 2022;DeZoort et al, 2002) and its diligence (Xie et al, 2003).…”
Section: Hypotheses Developmentmentioning
confidence: 99%